Defining Judicial Independence and Accountability Post Political Transition - Chandranegara, Ibnu Sina (Constitutional Review, 2019)
Indonesian constitutional reform after the fall of Soeharto?s New Order brings favorable direction for the judiciary. Constitutional guarantee of judicial independence as regulated in Art 24 (1) of the 1945 Constitution, has closed dark memories in the past. This article decides that the Judiciary is held by the Supreme Court and the judicial bodies below and a Constitutional Court. Such a strict direction of regulation plus the transformation of the political system in a democratic direction should bring about the implementation of the independent and autonomous judiciary. But in reality, even though in a democratic political system and constitutional arrangement affirms the guarantee of independence, but it doesn?t represent the actual situation. There are some problems that remain, such as (i) the absence of a permanent format regarding the institutional relationship between the Supreme Court, the Constitutional Court, and the Judicial Commission, and (ii) still many efforts to weaken judiciary through different ways such criminalization of judge. Referring to the problem above, then there are gaps between what "is" and what "ought", among others. First, by changing political configuration that tends to be more democratic, the judiciary should be more autonomous. In this context, various problems arise such as (i) disharmony in regulating the pattern of relations between judicial power actors, (ii) various attempts to criminalize judges over their decisions, and (iii) judicial corruption. Second, by the constitutional guarantee of the independence of the judiciary, there will be no legislation that that may reduce constitutional guarantee. However, there are many legislation or regulations that still not in line with a constitutional guarantee concerning judicial independence. This paper reviews and describes in-depth about how to implement constitutional guarantees of judicial independence after the political transition and conceptualize its order to strengthen rule of law in Indonesia